(3GSJQGJjLjI GSJHGb GdJgOjO hCKQgG Ydi GdCef Gdbhej GdCeQjcj HYO GdYGe (B2001s - (3GdbQjTj(B, (3eMeO eMSf RjOGfs ((3YeGf(B;(3YeGfs (3OGQ CeLO ddfTQ hGdJhRjY(B;(3EHUGQ fGTQhf h ehRYhfs, 2023)
(3jJVef gPG GdcJGH ehVhY GdGSJHGb hgh CeQ ege dfLGM Cj GSJQGJjLjI aj GdYGde, MjK JYO GSJQGJjLjI GSJHGb GdJgOjOGJ ef CaVd GdfXQjGJ hGdGSJQGJjLjGJ aj GdYGde hGdJj ef NdGdgG jJe GdYed Ydi JWhjQ GdChVGY GdeMdjI hGdOhdjI, ceG JVef GdcJGH GdELQGAGJ GdJj bGeJ HgG GdhdGjGJ GdeJMOI GdCeQjcjI dMeGjI CefgG GdeJYQV ddJgOjOGJ GdeJfhYI hcPdc Je YQV Cge edGeM SjGSI GdhdGjGJ GdeJMOI GdCeQjcjI aj GdfXGe GdOhdj(B.s
Keywords: (3GdCef Gdbhej (B- (3GdhdGjGJ GdeJMOI GdCeQjcjI (B- (3GdbQf (B21s; (3GdhdGjGJ GdeJMOI GdCeQjcjI (B- (3GdYdGbGJ GdNGQLjI (B- (3GdbQf (B21s